2016
DOI: 10.1016/j.ijadhadh.2016.03.023
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and micro-characterization of pathophysiological events on caries-affected dentin treated with glass-ionomer cements

Abstract: The aim of this study was to evaluate if mechanical cycling influences bioactivity and bond strength at the glass-ionomer cement-dentin interface, after load cycling.Microtensile bond strength (MTBS) was assessed with Ketac-Bond (conventional glass ionomer/GIC) or Vitrebond Plus (resin-modified/RMGIC), in sound dentin or in cariesaffected dentin (CAD). Debonded dentin surfaces were studied by field emission scanning electron microscopy (FESEM), and remineralization was evaluated through nanohardness (Hi) and Y… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 63 publications
(104 reference statements)
0
3
0
Order By: Relevance
“…Overall, the comparison between GICs and modified RMGICs has shown no significant differences, with small variations depending on the studies [ 34 ]. This result is of particular interest since, in studies assessing only fluoride release, it was concluded that the RMGICs had less remineralizing power.…”
Section: Discussionmentioning
confidence: 99%
“…Overall, the comparison between GICs and modified RMGICs has shown no significant differences, with small variations depending on the studies [ 34 ]. This result is of particular interest since, in studies assessing only fluoride release, it was concluded that the RMGICs had less remineralizing power.…”
Section: Discussionmentioning
confidence: 99%
“…Formation of a shallow hybrid layers (HL) (~1-2 µm depth) made of cement and collagen [2,3] definitely contribute to micro and nano-mechanical bonding [4,5]. A volume of demineralized/unprotected collagen remains at the bottom of the hybrid layer (BHL) [6]. This vulnerable unsupported collagen may become the sites for collagen hydrolysis by host-derived matrix metalloproteinases (MMPs) enzymes [7] or by other proteases from bacteria [8] that may trigger the interface degradation [3].…”
Section: Introductionmentioning
confidence: 99%
“…Resin-modified glass-ionomer cements (RMGIC) set, when mixed, through an acid-base reaction between ion-leachable glasses and polyalkenoic acids, as well as upon light-polymerization of water-soluble (metha)crylate, such as HEMA [9]. Phosphate and calcium and lower fractions of aluminum, sodium or strontium have been previously measured at the cement-dentin interface [6]. They become integrated in this porous, nonparticulate, poly(HEMA)-rich hydrogel layer [10], the absorption layer [11].…”
Section: Introductionmentioning
confidence: 99%